High-strength thermal shock resistant brick and preparation method thereof
By using high-strength thermal shock-resistant bricks composed of electromelt zirconium corundum, electromelt zirconium mullite, electromelt chromium oxide, nano-aluminum nitride powder and binding agent, the existing bricks have been solved by low bonding strength, poor wear resistance and resistance. The problem of poor thermal shock performance achieves high pressure resistance and excellent thermal shock resistance, which extends the service life.
Patent Information
- Application Number
- CN202411531140.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
AI Technical Summary
The existing high-strength thermal shock-resistant bricks have low bonding strength, poor wear resistance, and severe peeling damage. Although the chrome corundum bricks have high strength, their thermal shock resistance is poor, resulting in a shortened service life and affecting the improvement of smelting capacity.
High-strength thermal shock-resistant bricks composed of electromelt zirconium corundum, electromelt zirconium mullite, electromelt chromium oxide, nano-aluminum nitride powder and bonding agent (Norwegian lignin sulfonate), are used to dry mix and wet mill, Pressurized molding, drying and high-temperature firing process steps to form high-purity composite mineral phases to improve thermal shock and corrosion resistance.
It significantly improves the compressive strength and thermal shock resistance of high-strength thermal shock resistance, making it stable structure and firm bonding at high temperatures, and has good toughness in the emergency and heat state, which is not easy to damage, and extends its service life.
Smart Images

Figure BDA0005110507060000081
Abstract
Description
1. Technical field:
[0001] The invention belongs to the technical field of refractory materials, and particularly relates to a high-strength thermal shock resistant brick and a preparation method thereof. 2. Background technology:
[0002] High-strength thermal shock resistant bricks are a kind of refractory products with high strength and excellent thermal shock resistance. They are mainly used in the lining of non-ferrous intermittent smelting furnaces and the parts with large temperature fluctuations at the discharge port. The refractory bricks commonly used in these parts are traditional products, such as direct-bonded magnesia-chrome bricks, electric-melted semi-rebonded magnesia-chrome bricks, electric-melted rebonded magnesia-chrome bricks, chrome corundum bricks, etc. At present, the existing magnesia-chrome bricks have low bonding strength, poor wear resistance, and severe spalling damage. Although chrome corundum bricks have high strength, they have poor thermal shock resistance, which shortens the service life and affects the improvement of smelting capacity. Therefore, it is urgent to develop a refractory product with high strength and superior thermal shock resistance. 3. Summary of the invention:
[0003] The technical problem to be solved by the present invention is: in view of the problems existing in the prior art of high-strength thermal shock resistant bricks, the present invention provides a high-strength thermal shock resistant brick for the lining and discharge port of a non-ferrous intermittent smelting furnace and a preparation method thereof. Through the technical scheme of the present invention, the compressive strength and thermal shock resistance of the obtained high-strength thermal shock resistant product can be significantly improved, so that the structure is stable and the bonding is firm at high temperature, the toughness is good under rapid cooling and rapid heating, and it is not easy to be damaged; and the manufacturing process is conventional and easy to construct.
[0004] In order to solve the above problems, the technical solution adopted by the present invention is:
[0005] The invention provides a high-strength thermal shock resistant brick, which is mainly composed of 8-12% of fused zirconium corundum with a particle size of 5-3mm, 20-24% of fused zirconium corundum with a particle size of 3-1mm, 12-16% of fused zirconium corundum with a particle size of 1-0mm, 16-20% of fused zirconium mullite with a particle size of 3-1mm, 6-10% of fused zirconium mullite with a particle size of 1-0mm, 18-22% of fused zirconium mullite with a particle size of ≤0.088mm and 6-10% of fused chromium oxide with a particle size of 325 mesh, and in addition, nano aluminum nitride powder accounting for 1-3% of the total weight of each raw material and a binder accounting for 3-4% of the total weight of each raw material are added.
[0006] According to the above-mentioned high-strength thermal shock resistant bricks, the mass percentage of Al2O3 in the fused zirconium corundum is ≥70%, and the mass percentage of ZrO2 is ≥20%.
[0007] According to the above-mentioned high-strength thermal shock resistant bricks, the mass percentage of Al2O3 in the fused zirconium mullite is ≥60%, and the mass percentage of ZrO2 is ≥28%.
[0008] According to the above-mentioned high-strength thermal shock resistant bricks, the mass percentage of Cr2O3 in the fused chromium oxide is ≥99%.
[0009] According to the above-mentioned high-strength thermal shock resistant bricks, the binder is Norwegian calcium lignin sulfonate (sold by Shanghai Jingming Chemical Co., Ltd. and Nanjing Qicheng New Materials Co., Ltd.).
[0010] In addition, a method for preparing a high-strength thermal shock resistant brick is provided, the method comprising the following steps:
[0011] a. Weigh various raw materials according to the ratio of the above-mentioned high-strength thermal shock resistant bricks;
[0012] b. Put five kinds of granular materials weighed, namely, fused zirconium corundum with a particle size of 5-3 mm, fused zirconium corundum with a particle size of 3-1 mm, fused zirconium corundum with a particle size of 1-0 mm, fused zirconium mullite with a particle size of 3-1 mm, and fused zirconium mullite with a particle size of 1-0 mm, into a mixer for dry mixing to obtain a dry mixed material;
[0013] c. Add a binder to the obtained dry mixed material, place it in a mixer and stir it evenly to obtain a wet granular mixture;
[0014] d. The obtained wet particle mixture is sent to a planetary wet mill for wet milling (via belt conveyor). During the wet milling process, fused zirconium mullite with a particle size of ≤0.088 mm, fused chromium oxide with a particle size of 325 mesh, and nano-aluminum nitride powder are added and mixed and milled for 8 to 10 minutes to obtain a semi-dry plastic mud material;
[0015] e. Adding the obtained semi-dry plastic mud into a brick mold for pressure molding to obtain a brick;
[0016] f. Drying the obtained bricks until the moisture content of the obtained bricks is ≤0.6%;
[0017] g. The bricks obtained after drying are fired in a (fully automatic computer-controlled) high-temperature tunnel kiln at a firing temperature of 1600°C and a heat preservation time of 10 to 12 hours. After firing, high-strength thermal shock-resistant bricks are obtained.
[0018] According to the above-mentioned method for preparing high-strength thermal shock resistant bricks, the dry mixing time in step b is 2 to 3 minutes; and the stirring time in step c is 3 to 5 minutes.
[0019] According to the above-mentioned method for preparing high-strength thermal shock resistant bricks, a 630t electric screw press is used during the pressure molding in step e; the volume density of the obtained brick blank is 2.98-3.05g / cm3.
[0020] According to the above-mentioned method for preparing high-strength thermal shock resistant bricks, during drying in step f, the drying temperature is controlled to be 110-120° C. and the drying time is controlled to be 24 hours.
[0021] According to the preparation method of the high-strength thermal shock resistant bricks, the high-strength thermal shock resistant bricks obtained in step g contain Al2O3≥60%, ZrO2≥20%, and Cr2O3≥5%.
[0022] The nano aluminum nitride powder used in the present invention belongs to a high-grade synthetic material; the fused zirconium mullite fine powder and the nano aluminum nitride powder used play the role of toughening agents; the binder used is Norwegian calcium lignin sulfonate (sold by Shanghai Jingming Chemical Co., Ltd. and Nanjing Qicheng New Materials Co., Ltd.). When the binder is used, it is first mixed with 50-60°C water to form a calcium lignin sulfonate solution with a specific gravity of 1.26-1.28 (its viscosity is 150-180 Pa.s).
[0023] The technical solution of the present invention is to prepare high-strength thermal shock resistant bricks, starting with the selection of raw materials. First, the skeleton selects fused zirconium corundum with excellent hardness and strength and fused zirconium mullite with excellent thermal shock resistance as the main raw materials, strengthens the matrix and optimizes the organizational structure. The fused chromium oxide ultrafine powder that can cause phase change during the sintering process is added, and nano-aluminum nitride powder is added to enhance the bonding strength; the process formula is determined by reasonable matching and optimized combination. The binder adopts a solution prepared by Norwegian imported calcium lignin sulfonate with stronger bonding properties. In the production process, suitable mixing and grinding equipment and molding equipment are selected, and the outer dimensions, volume density and unit weight of the brick blank are strictly controlled. Through the drying and loading links, the high-temperature tunnel kiln is automatically controlled by the computer to form a firm composite crystal phase, which greatly improves the compressive strength and thermal shock resistance of the product, replacing the traditional products of direct bonded bricks, semi-rebonded magnesia-chrome bricks, fused rebonded magnesia-chrome bricks, and chrome corundum bricks, and the service life is significantly improved.
[0024] The skeleton of the high-strength thermal shock-resistant brick of the product of the present invention adopts fused zirconium corundum and fused zirconium mullite which causes phase change at high temperature to improve the thermal shock resistance; the matrix is added with fused zirconium mullite fine powder and fused chromium oxide ultrafine powder to enhance the toughness, and nano aluminum nitride powder is added. Aluminum nitride is an atomic crystal and a diamond-like nitride. It has good volume stability at high temperature, small thermal expansion coefficient, and high bonding strength. It is a good heat shock-resistant material. The high-strength thermal shock-resistant brick obtained by optimizing the combination of several high-toughness materials not only has high compressive strength, but also has excellent thermal shock and erosion resistance. It is used in non-ferrous intermittent smelting furnaces and discharge ports to effectively extend the service life.
[0025] The positive beneficial effects of the present invention are:
[0026] 1. The fused zirconium corundum and fused chromium oxide used in the high-strength thermal shock resistant bricks of the present invention are both high-purity raw materials. By adding fused zirconium mullite fine powder that improves thermal shock performance at high temperature, fused chromium oxide that causes phase change to improve toughness, and adding nano-aluminum nitride powder that enhances bonding performance, a grid-like and firmly bonded composite mineral phase is formed at high temperature, which significantly improves the thermal shock resistance and corrosion resistance of the product. It is applied to non-ferrous intermittent smelting furnaces and discharge ports to effectively extend the service life.
[0027] 2. The technical solution of the present invention, through the optimization of the raw materials for strengthening and toughening by electrofusion synthesis, the reasonable matching of each particle size, the reasonable use of ultrafine nano aluminum nitride powder and the optimized design of the process, makes the prepared high-strength thermal shock resistant bricks truly achieve high strength and thermal shock resistance (test results are shown in Table 1). 4. Specific implementation methods:
[0028] The technical solution of the present invention is described clearly and completely below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the technical solution of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] In the following embodiments, the Al2O3 mass percentage of the fused zirconium corundum used is ≥70%, and the ZrO2 mass percentage is ≥20%; the Al2O3 mass percentage of the fused zirconium mullite is ≥60%, and the ZrO2 mass percentage is ≥28%; the Cr2O3 mass percentage of the fused chromium oxide is ≥99%; and the binder is a calcium lignin sulfonate solution prepared from Norwegian calcium lignin sulfonate and water at 50-60°C with a specific gravity of 1.26-1.28 and a viscosity of 150-180 Pa.s.
[0030] Embodiment 1:
[0031] The high-strength heat-shock-resistant brick of the present invention is composed, expressed in percentage by mass, of 11% of fused zirconium corundum with a particle size of 5-3mm, 22% of fused zirconium corundum with a particle size of 3-1mm, 15% of fused zirconium corundum with a particle size of 1-0mm, 17% of fused zirconium mullite with a particle size of 3-1mm, 9% of fused zirconium mullite with a particle size of 1-0mm, 19% of fused zirconium mullite with a particle size of ≤0.088mm and 7% of fused chromium oxide with a particle size of 325 mesh; in addition, 2% of the total weight of various raw materials and 3.5% of the total weight of each raw material are added as a binder.
[0032] Embodiment 2:
[0033] The high-strength heat-shock-resistant brick of the present invention is composed, expressed in percentage by mass, of 10% of fused zirconium corundum with a particle size of 5-3mm, 22% of fused zirconium corundum with a particle size of 3-1mm, 14% of fused zirconium corundum with a particle size of 1-0mm, 18% of fused zirconium mullite with a particle size of 3-1mm, 8% of fused zirconium mullite with a particle size of 1-0mm, 20% of fused zirconium mullite with a particle size of ≤0.088mm and 8% of fused chromium oxide with a particle size of 325 mesh; in addition, 2% of the total weight of various raw materials and 3.5% of the total weight of each raw material are added as a binder.
[0034] Embodiment 3:
[0035] The high-strength heat-shock-resistant brick of the present invention is composed, expressed in percentage by mass, of 8% of fused zirconium corundum with a particle size of 5-3mm, 24% of fused zirconium corundum with a particle size of 3-1mm, 12% of fused zirconium corundum with a particle size of 1-0mm, 20% of fused zirconium mullite with a particle size of 3-1mm, 6% of fused zirconium mullite with a particle size of 1-0mm, 22% of fused zirconium mullite with a particle size of ≤0.088mm and 8% of fused chromium oxide with a particle size of 325 mesh; in addition, 2% of nano aluminum nitride powder accounting for the total weight of various raw materials and 3.5% of a binder accounting for the total weight of each raw material are added.
[0036] Embodiment 4:
[0037] The high-strength heat-shock-resistant brick of the present invention is composed, expressed in percentage by mass, of 9% of fused zirconium corundum with a particle size of 5-3mm, 23% of fused zirconium corundum with a particle size of 3-1mm, 13% of fused zirconium corundum with a particle size of 1-0mm, 19% of fused zirconium mullite with a particle size of 3-1mm, 7% of fused zirconium mullite with a particle size of 1-0mm, 20% of fused zirconium mullite with a particle size of ≤0.088mm and 9% of fused chromium oxide with a particle size of 325 mesh; in addition, 2% of the total weight of various raw materials and 3.5% of the total weight of each raw material are added as a binder.
[0038] The preparation method of the high-strength thermal shock resistant bricks described in Examples 1 to 5 of the present invention comprises the following detailed steps:
[0039] a. Weigh various raw materials according to the proportion of the high-strength thermal shock resistant bricks described in any one of Examples 1 to 5;
[0040] b. Place five kinds of granular materials, namely, fused zirconium corundum with a particle size of 5-3 mm, fused zirconium corundum with a particle size of 3-1 mm, fused zirconium corundum with a particle size of 1-0 mm, fused zirconium mullite with a particle size of 3-1 mm, and fused zirconium mullite with a particle size of 1-0 mm, in a mixer and dry-mix for 3 minutes to obtain a dry-mixed material;
[0041] c. Add a binder to the obtained dry mixed material, place it in a mixer and stir it for 5 minutes to obtain a wet granular mixture;
[0042] d. The obtained wet particle mixture is sent to a planetary wet mill for wet milling (via belt conveyor). During the wet milling process, fused zirconium mullite with a particle size of ≤0.088 mm, fused chromium oxide with a particle size of 325 mesh, and nano-aluminum nitride powder are added and mixed and milled for 10 minutes to obtain a semi-dry plastic mud material;
[0043] e. Add the obtained semi-dry plastic mud into a brick mold, and use a 630t electric screw press to press and form a brick; the obtained brick has a bulk density of 2.98 to 3.05 g / cm3;
[0044] f. Send the obtained bricks into a dryer, the temperature of the dryer is controlled at 110-120°C, the drying time is 24 hours, and the moisture content of the obtained bricks is ≤0.6%;
[0045] g. The dried bricks are fired in a fully automatic computer-controlled high-temperature tunnel kiln at a temperature of 1600°C and a heat preservation time of 12 hours. After firing, high-strength thermal shock-resistant bricks are obtained.
[0046] The relevant performance test data of the product prepared by using the mixing ratio of any of the high-strength thermal shock resistant bricks described in Examples 1 to 5 of the present invention are detailed in Table 1.
[0047] Comparative Example 1:
[0048] A refractory brick, expressed in percentage by mass, is composed of 10% fused zirconium corundum with a particle size of 5-3mm, 40% fused zirconium corundum with a particle size of 3-1mm, 14% fused zirconium corundum with a particle size of 1-0mm, 8% fused zirconium mullite with a particle size of 1-0mm, 20% fused zirconium mullite with a particle size of ≤0.088mm and 8% fused chromium oxide with a particle size of 325 mesh; in addition, 2% of nano aluminum nitride powder accounting for the total weight of various raw materials and 3.5% of a binder accounting for the total weight of each raw material are added (the fused zirconium mullite with a particle size of 3-1mm is not used in this comparative example 1).
[0049] Comparative Example 2:
[0050] A refractory brick, expressed in percentage by mass, is composed of 10% fused zirconium corundum with a particle size of 5-3mm, 22% fused zirconium corundum with a particle size of 3-1mm, 22% fused zirconium corundum with a particle size of 1-0mm, 18% fused zirconium mullite with a particle size of 3-1mm, 20% fused zirconium mullite with a particle size of ≤0.088mm and 8% fused chromium oxide with a particle size of 325 mesh; in addition, 2% of nano aluminum nitride powder accounting for the total weight of various raw materials and 3.5% of a binder accounting for the total weight of each raw material are added (the fused zirconium mullite with a particle size of 1-0mm is not used in this comparative example 2).
[0051] Comparative Example 3:
[0052] A refractory brick, expressed in percentage by mass, is composed of 10% fused zirconium corundum with a particle size of 5-3mm, 22% fused zirconium corundum with a particle size of 3-1mm, 14% fused zirconium corundum with a particle size of 1-0mm, 18% fused zirconium mullite with a particle size of 3-1mm, 8% fused zirconium mullite with a particle size of 1-0mm, 20% fused zirconium mullite with a particle size of ≤0.088mm and 8% fused chromium oxide with a particle size of 325 mesh; in addition, a binder accounting for 3.5% of the total weight of the raw materials is added (nano aluminum nitride powder is not added in this comparative example 3).
[0053] The preparation method of the refractory bricks described in Comparative Examples 1 to 3 is the same as the preparation method of the high-strength thermal shock resistant bricks described in Examples 1 to 5. The relevant performance test data of the products prepared by using the proportions of the refractory bricks described in Comparative Examples 1 to 3 are shown in Table 1.
[0054] Table 1 Relevant performance index test data of the products prepared in Examples 1-4 and Comparative Examples 1-3
[0055]
[0056] It can be seen from the data in Table 1 that the relevant performance technical indicators of the products prepared in Examples 1-4 of the present invention can meet the use of intermittent non-ferrous smelting furnace linings and discharge ports. In comparison, the particle grading of Example 2 is the most reasonable, and the addition amount of various particle sizes is the optimal addition amount selected after experiments. The thermal shock resistant materials fused zirconium corundum and fused zirconium mullite are also the best raw materials and the best addition amounts selected after experiments. The preferred embodiment 2 helps to improve the volume density and compressive strength of the product, especially the highest compressive strength and the best thermal shock resistance under the same experimental conditions. It can be seen from the experimental data of the embodiments and comparative examples that each material selected in the embodiments of the present invention has its specific role, and the lack of any of them will affect the technical indicators and performance of the product.
Claims
1. A high-strength thermal shock resistant brick, characterized in that: Expressed in percentage by mass, the high-strength thermal shock resistant brick is mainly composed of 8-12% of fused zirconium corundum with a particle size of 5-3mm, 20-24% of fused zirconium corundum with a particle size of 3-1mm, 12-16% of fused zirconium corundum with a particle size of 1-0mm, 16-20% of fused zirconium mullite with a particle size of 3-1mm, 6-10% of fused zirconium mullite with a particle size of 1-0mm, 18-22% of fused zirconium mullite with a particle size of ≤0.088mm and 6-10% of fused chromium oxide with a particle size of 325 mesh; in addition, nano aluminum nitride powder accounting for 1-3% of the total weight of each raw material and a binder accounting for 3-4% of the total weight of each raw material are added.
2. The high-strength thermal shock resistant brick according to claim 1 is characterized in that: The mass percentage of Al2O3 in the fused zirconium corundum is ≥70%, and the mass percentage of ZrO2 is ≥20%.
3. The high-strength thermal shock resistant brick according to claim 1 is characterized in that: The mass percentage of Al2O3 in the fused zirconium mullite is ≥60%, and the mass percentage of ZrO2 is ≥28%.
4. The high-strength thermal shock resistant brick according to claim 1 is characterized in that: The mass percentage of Cr2O3 in the fused chromium oxide is ≥99%.
5. The high-strength thermal shock resistant brick according to claim 1 is characterized in that: The binder is Norwegian calcium lignin sulfonate.
6. A method for preparing high-strength thermal shock resistant bricks, characterized in that: The preparation method comprises the following steps: a. Weigh various raw materials according to the proportion of the high-strength thermal shock resistant bricks described in claim 1; b. Put five kinds of granular materials weighed, namely, fused zirconium corundum with a particle size of 5-3 mm, fused zirconium corundum with a particle size of 3-1 mm, fused zirconium corundum with a particle size of 1-0 mm, fused zirconium mullite with a particle size of 3-1 mm, and fused zirconium mullite with a particle size of 1-0 mm, into a mixer for dry mixing to obtain a dry mixed material; c. Add a binder to the obtained dry mixed material, place it in a mixer and stir it evenly to obtain a wet granular mixture; d. The obtained wet granular mixture is sent to a planetary wet mill for wet milling. During the wet milling process, fused zirconium mullite with a particle size of ≤0.088 mm, fused chromium oxide with a particle size of 325 mesh, and nano-aluminum nitride powder are added and mixed and milled for 8 to 10 minutes to obtain a semi-dry plastic mud material; e. Adding the obtained semi-dry plastic mud into a brick mold for pressure molding to obtain a brick; f. Drying the obtained bricks until the moisture content of the obtained bricks is ≤0.6%; g. The dried bricks are fired in a high-temperature tunnel kiln at a temperature of 1600°C and a heat preservation time of 10 to 12 hours. After firing, high-strength thermal shock-resistant bricks are obtained.
7. The method for preparing high-strength thermal shock resistant bricks according to claim 6, characterized in that: The dry mixing time in step b is 2 to 3 minutes; the stirring time in step c is 3 to 5 minutes.
8. The method for preparing high-strength thermal shock resistant bricks according to claim 6, characterized in that: The pressure molding in step e is performed using a 630t electric screw press; the volume density of the obtained brick is 2.98-3.05g / cm3.
9. The method for preparing high-strength thermal shock resistant bricks according to claim 6, characterized in that: During drying in step f, the drying temperature is controlled to be 110-120° C. and the drying time is 24 hours.
10. The method for preparing high-strength thermal shock resistant bricks according to claim 6, characterized in that: The high-strength thermal shock-resistant bricks obtained in step g contain Al2O3≥60%, ZrO2≥20%, and Cr2O3≥5%.
Citation Information
Patent Citations
Preparation method of zircon corundum brick containing chromic oxide
CN104446564A
Steel ladle carbon-free pouring nozzle and preparation method thereof
CN110642633A
Sintered aluminum-chromium-zirconium sliding plate brick for copper smelting anode furnace and preparation method of sintered aluminum-chromium-zirconium sliding plate brick
CN110746180A
Corrosion-resistant zirconium mullite product for soft magnetic ferrite nitrogen kiln and preparation method of corrosion-resistant zirconium mullite product
CN115448739A
Refractory material based on chromium corundum, a chromium corundum brick and the use of said brick
US6352951B1
Cited By
High-purity corundum brick with high thermal shock resistance and preparation method thereof
CN120483693A